Upaya Meningkatkan Minat Siswa terhadap Kegiatan Ekstrakurikuler Seni Teater dengan Menerapkan Metode Drill di SMAN 4 Tebo - Enda Surnia; Hengki Armez Hidayat (Dinasti Research, 2023)
The purpose of this research is to describe efforts to increase students' interest in theater extracurriculars by applying the drill method at SMAN 4 Tebo. This type of research is qualitative research with a participatory approach. The research instrument was the researcher himself and assisted by supporting instruments. The supporting instruments that the researchers used in this study were in the form of documentation from field data recording devices in the form of activity photos and observation notes. Data collection techniques were carried out by means of observation, literature study, interviews and documentation. The steps to analyze the data are collecting data, identifying data, classifying data and drawing conclusions. The results showed that the efforts made by using the concept of musical drama by applying the drill method could increase students' interest in the Theater Arts extracurricular at SMAN 4 Tebo. Another effort is to give appreciation to students. The increase was seen based on indicators of interest, namely feelings of pleasure, student involvement (active), interest, and student attention. The use of the concept of musical drama by applying the drill method in Theater Arts extracurricular activities can make the atmosphere of this activity active and structured. This can be seen through the behavior of students contained in the indicators of student interest which are getting better and increasing so that they are able to increase student interest in the Theater Arts extracurricular.